1997
DOI: 10.1152/physrev.1997.77.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial sodium channels: function, structure, and regulation

Abstract: The apical (outward-facing) membranes of high-resistance epithelia contain Na+ channels, traditionally identified by their sensitivity to block by the K(+)-sparing diuretic amiloride. Such channels have been characterized in amphibian skin and urinary bladder, renal collecting duct, distal colon, sweat and salivary glands, lung, and taste buds. They mediate the first step of active Na+ reabsorption and play a major role in the maintenance of electrolyte and water homeostasis in all vertebrates. In the past, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
1,015
5
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,078 publications
(1,059 citation statements)
references
References 0 publications
37
1,015
5
2
Order By: Relevance
“…This current was completely inhibited by amiloride (Fig. 3A), a blocker of ENaC (30,31). Stimulation by cold temperature was not dependent on voltage; a temperature of 10°C increased Na ϩ current at all voltages tested (Ϫ120 to ϩ40 mV, Fig.…”
Section: Resultsmentioning
confidence: 87%
“…This current was completely inhibited by amiloride (Fig. 3A), a blocker of ENaC (30,31). Stimulation by cold temperature was not dependent on voltage; a temperature of 10°C increased Na ϩ current at all voltages tested (Ϫ120 to ϩ40 mV, Fig.…”
Section: Resultsmentioning
confidence: 87%
“…touch, pain and thermoregulation) (Oláh et al, 2012). For example, ENaC, an epithelial sodium channel with a key role in regulating the transport of sodium ions in electrically tight epithelia such as the renal collecting duct (Garty and Palmer, 1997), is also expressed in the epidermis and cultured keratinocytes (Brouard et al, 1999), and appears to be required for the directional migration of keratinocytes in an electric field, indicating a role for ENaC in wound healing (Yang et al, 2013). Utilising next-generation sequencing technologies, numerous new genes that are involved in inherited skin diseases are being identified.…”
Section: Perspectivesmentioning
confidence: 99%
“…The epithelial Na + channel (ENaC) located in the distal nephrons of the kidney, and in the lung, sweat glands and colon is an essential component of the body's salt-and-water-regulation system [1]. The Na + channel is composed of three subunits called α, β and γ that share similar primary sequences [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Staub et al [23] reported that the WW domains of the ubiquitin-protein ligase Nedd4 [neuronal precursor cell expressed developmentally downregulated (gene 4)] bind to the PPPXY (PY) motifs found in the C-terminus of all three subunits, and that the α and γ subunits Abbreviations used : ENaC, epithelial Na + channel ; hENaC, human ENaC ; αhENaC, α subunit of hENaC ; GST, glutathione S-transferase ; SH3, Src homology 3 ; PY motif, PPPXY motif ; MDCK, Madin-Darby canine kidney ; HA, haemagglutinin ; hNedd4, human Nedd4 ; WWP, WW-domain-containing protein. 1 To whom correspondence should be addressed (e-mail fiona.mcdonald!vuw.ac.nz).…”
Section: Introductionmentioning
confidence: 99%